The Overcoming difficulties in donor selection for pediatric allogeneic transplantation in a resource- limited country: Overcoming difficulties in donor selection for pediatric allogeneic transplantation in a resource -limited country - Barriga, Francisco; Wietstruck, Angelica; Jara, Veronica; Gutierrez, Catherine (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
Objective: Centers in resource-limited countries face significant challenges in performing unrelated donor allogeneic stem cell transplantation. We analyze the outcome of concrete actions taken by our program since 2008 to gain access to worldwide transplant donors, select and procure the preferred donor for our patients, and perform the transplant timely. Methods: We focused on three aspects to gain unlimited access to unrelated donors: hiring and training dedicated nurse coordinators, establishing fluid communication and collaboration with donor registries and cord blood banks, and careful planning of the transplant procedure to avoid delays. We describe the evolution of donor choice since 2008 and the time to transplantation between related (matched sibling and haploidentical) and unrelated (adult and cord blood) donors. Results: We transplanted 238 children between 2008 and 2022. Transplant activity increased from 28 procedures in 2008-2010 to 85 in 2020-2022, mainly at the expense of unrelated donors. The proportion of unrelated donors between both periods increased from 14% to 65% as cord blood usage decreased from 65% to 9% (p<0,001). DKMS donor centers provided 60% of the products. The mean time to transplantation was 68 days for related donors (MSD and haploidentical) and 74 days for unrelated donors (MUD, MMUD, UCB). Conclusion: Despite practicing in a limited resource setting, specific actions allowed us to overcome difficulties in search, procurement, and timely transplantation.